Analysis of Differences in Share Performance between SOEs and Non-SOEs Based on Short-Term Underpricing and Long-Term Underperformance - Novriska Mointi; Yayu Isyana Pongoliu (Jambura Science of Management, 2020)
This study aims to determine the differences in the performance of shares of SOEs and Non-SOEs companies that conduct IPOs on the Indonesia Stock Exchange in the period 2010-2014 based on short-term underpricing and long-term underperformance. Sampling is done by using purposive sampling technique. Data analysis techniques used the independent sample parametric test and the non-parametric difference test mann whitney u test. The results showed that there were no differences in the performance of shares of SOE and Non-SOE companies conducting IPOs on the Indonesia Stock Exchange in the 2010-2014 period based on short-term underpricing. This means that in the short term investments in shares of Non-BUMN companies are more profitable for investors and are detrimental to the company because the funds obtained are less. But in testing based on long-term underperformance, the results of the study showed that there were differences in the performance of the shares of SOE and Non-SOE companies conducting IPOs on the IDX for the 2010-2014 period. This shows that BUMN companies have better performance than Non-BUMN companies, because government ownership gives more value and can operate in various sectors.